REVIEW PAPER ON AUTOMATIC PLANT WATER SYSTEM (International Journal of Engineering Management Science, 2024)
In diurnal operations related to husbandry or gardening watering is the most important practice and the most labor- ferocious task. No matter whichever rainfall it is, either too hot and dry or too cloudy and wet, you want to be suitable to control the quantum of water that reaches your shops. Ultramodern watering systems could be effectively used to water shops when they need it. But this homemade process of soddening requires two important aspects to be considered when and how important to water. In order to replace homemade conditioning and making gardener's work lightly, we've produce automatic factory soddening system. By adding automated factory watering system to the theater or agrarian field, you'll help all of the shops reach their fullest eventuality as well as conserving water. Using sprinklers drop emitters, or a combination of both, we've design a system that's ideal for every factory in the yard. For perpetration of automatic factory soddening system, we've used combination of sprinkler systems, pipes, and snoots. In this paper we've used ATmega328 microcontroller. It's programmed to sense humidity position of shops at particular case of time, if the humidity content is lower than specified threshold which is predefined according to particular factory's water need also asked quantum of water is supplied till it reaches threshold. Generally, shops need to be doused twice a day, morning and evening. Therefore, the microcontroller is programmed to water shops two times per day. System is designed in such a way that it reports its current state as well as reminds the stoner to add water to the tank. All this announcements are made through mobile operation. We hope that through this prototype we all can enjoy having shops, without being upset about absent or obliviousness.
Keywords: Arduino, Microcontroller, IR sensor, Voltage sensor, Relay, Battery